The Prospective Influence of Trait Alexithymia on Intrusive Memories: What Is the Role of Emotional Recognition Memory? - Sopp, M. Roxanne; Brueckner, Alexandra H.; Michael, Tanja (Frontiers in Psychology, 2019)
Posttraumatic stress disorder (PTSD) is often considered to be a disorder of memory as patients suffer from fragmented uncontrollable memories (intrusions) whilst experiencing difficulties in intentionally retrieving details of the traumatic event. Recent research suggests that trait-related deficits in the identification of emotional states (alexithymia) may impact emotional memory processes in a way that promotes intrusion formation in PTSD. Therefore, we investigated the influence of alexithymia on intrusive re-experiencing and emotional recognition memory in a prospective study. Twenty-six healthy participants took part in a laboratory experiment, which combined two independent paradigms. In the first session, participants were exposed to a traumatic film. In the second session, they were subjected to an episodic memory paradigm comprising neutral and emotional stimuli. In between both sessions, participants recorded intrusive memories of the film. Individuals with higher trait alexithymia reported an increased number of intrusions on the day of film presentation. Moreover, analyses of memory performance revealed a negative correlation between alexithymia and emotional recognition memory. Further analyses suggest that reduced emotional recognition memory, as evident in individuals with higher trait alexithymia, may, in turn, be associated with enhanced intrusive re-experiencing. As such, the current findings provide important indications regarding the role of alexithymia in emotional learning and PTSD.